Girls in IT: intentionally self-excluded or products of high school as a site of exclusion?. Issue 3 (8th December 2020) - Vainionpää, Fanny; Kinnula, Marianne; Iivari, Netta; Molin-Juustila, Tonja
Abstract : Purpose: The low number of women in the information technology (IT) field is a concern. The purpose of this paper is to examine the factors behind the exclusion of girls from the IT field. Design/methodology/approach: The present work includes a narrative literature review and an exploratory interview study with ten girls and six study guidance counsellors (GCs) from Finnish senior high schools. Using the nexus analysis as a theoretical lens, the authors examined the exclusion of girls from IT. Findings: Earlier literature directed attention to the cultural norms, assumptions and stereotypes still prevalent in society and the lack of role models and positive media as factors contributing to girls excluding themselves from the IT field. In this research study's data, the authors not only found evidence of the unintentional exclusion of girls from IT by others but also by the girls themselves. Findings of this research study illustrate the various discourses, actors and their interactions, their background and history-related factors affecting girls' career choices. The novelty of this study is in approaching high school as a site of exclusion, where problematic discourses, interactions and histories come together, reproducing exclusion of girls from the IT field. Originality/value: The authors contribute with a literature review of the research study on gender and IT and the inclusion/exclusion dynamics around IT. Using the nexus analysis, the authors identify the exclusion dynamics in this complex social issue. Several decades of research have shown that the inclusion of women remains low in IT disciplines. In this study, high schools are viewed as sites of exclusion, engendering a prevalent lack of information and education on the field. The authors offer novel insights into the role of curriculum, GCs and online information excluding girls from the IT field.